2015
DOI: 10.11113/jt.v77.6734
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Activity of Mangrove Soil Actinomycetes Isolated From Tanjung Lumpur, Kuantan

Abstract: Actinomycetes are biotechnologically important for their unrivalled capacity to produce bioactive secondary metabolites. Although thousands of antibiotics have been discovered from actinomycetes, these represent only a small fraction of the entire reservoir. Thus, screening of actinomycetes from poorly studied environment is a valuable attempt. In the present study, an effort was made to isolate, identify and evaluate the antimicrobial activities of actinomycetes from Tanjung Lumpur Mangrove Forest of Pahang, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Interestingly enough, these authors demonstrated its antimicrobial ability against some bacteria and fungi. Actinophytocola sp., in addition to other actinomycetes, has also been demonstrated to inhibit the growth of well-known human pathogens ( B. subtilis and S. aureus ) 36 . Finally, Actinophytocola gilvus was recently isolated from extremely dry conditions, from a soil crusts sample collected in the Tengger Desert in China 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, these authors demonstrated its antimicrobial ability against some bacteria and fungi. Actinophytocola sp., in addition to other actinomycetes, has also been demonstrated to inhibit the growth of well-known human pathogens ( B. subtilis and S. aureus ) 36 . Finally, Actinophytocola gilvus was recently isolated from extremely dry conditions, from a soil crusts sample collected in the Tengger Desert in China 37 .…”
Section: Discussionmentioning
confidence: 99%